Performance comparison analysis of aes-256 sha-256-hmac, aes-256 md5-hmac, 3des sha-256-hmac and 3des-md5-hmac on ipsec vpn using gns3 / Mohd Hilman Lukman - Lukman, Mohd Hilman (2016)
Encryption algorithm will take advantage of advance computer hardware in term of processing and memory capacity. Secure connection can be established between two points within public internet infrastructure. To not compromise the resources of end terminal, this encryption and decryption process is done at layer 3 network. However performance of encryption needs to be tested as so many encryption algorithms in the market. This paper presented performance comparison analysis between two encryption algorithms and two integrity algorithms. The performances of the algorithm are compared by monitoring the download speed or throughput of every algorithm. By varying the algorithm, file size and protocol, every throughput is compared. Combination algorithm AES-256 SHA-256-HMAC has the highest throughput among others. The analysis also found that FTP performs better than HTTP. All the experiments are using GNS3.